Dancy Tangerine: HS169/CH074, 6/2018 - Jackson, L.K.; Futch, Stephen H. (EDIS, 2018)
This document is about Dancy, one of the oldest tangerine varieties known in Florida. The variety originated in 1867 from a seed of Moragne tangerine in the grove of Colonel F. L. Dancy of Orange Mills. Dancy has been a very popular variety over the years but is no longer widely planted due to a number of production problems that will be discussed later. There are still a few groves of Dancy as well as numerous dooryard trees, but this variety has been replaced over the years by new tangerine hybrids such as Robinson, Sunburst, and Honey (Murcott). First published in Sept. 1993